IMPLEMENTASI KEBIJAKAN BUPATI TENTANG PEMBELAJARAN TATAP MUKA TERBATAS PADA MASA PANDEMI CORONAVIRUS DISEASE OF 2019DI SMP NEGERI 1 JEPON KABUPATEN BLORA JAWA TENGAH - Sulasih Sulasih (Master of Public Administration, Universitas Slamet Riyadi, 2022)
Education is one of the most important aspects in life in order to form qualityhuman resources and be able to keep up with the current development of anincreasingly advanced era. The purpose of the study was to describe theimplementation of the Regent's Policy on Limited Face-to-Face Learning at SMPNegeri 1 Jepon during the 2019 Coronavirus Disease Pandemic, Blora Regency,Central Java. According to Edwards III, there are four factors that influencepublic policy, namely communication, resources, disposition and bureaucraticstructure.. This study uses a qualitative method with data collection techniquesthrough interviews and documentation on school residents.The results showedthat there was communication, resources, disposition and bureaucratic structure.The conclusion of the Implementation of the Regent's Policy on Limited Face-to-Face Learning at SMP Negeri 1 Jepon during the 2019 Coronavirus DiseasePandemic, Blora Regency, Central Java, is good.Keywords: Communication, resources, disposition, bureaucratic structure.